TEPHES' SITUATIONAL LEADERSHIP IN SPECIAL SCHOOLS DURING THE COVID-19 PANDEMIC - Dian Pratiwi; Nora Saiva Jannana; Adhi Setiawan (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
COVID-19 has generated significant management issues, notably in school leadership. Special schools demand leadership innovation so that learning activities stay optimal. This paper addresses situational leadership in Children with Special Needs (ABK) at SLB Negeri 2 Yogyakarta utilizing qualitative description and data collection through interviews, observation, and recording. A purposive sample of informants was used, and they were classified as important, primary, and supporting informants. Data analysis processes include transcripts, coding, grouping, comparing, contrasting, and interpretation. The findings of the SLB situational leadership research take into account the investigation of technology, economics, policy, health, environmental and social (TEPHES) factors in school decision-making in the Pandemic-19 scenario.